2013
DOI: 10.1016/j.seizure.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Use of pregabalin for nonconvulsive seizures and nonconvulsive status epilepticus

Abstract: Pregabalin may be safe option for add-on treatment for nonconvulsive seizures in critically ill patients when conventional therapy fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Swisher and co-workers reported a success rate of 52% for pregabalin. 2 However, they included patients with acute repetitive seizures as well as patients with post-hypoxic SE, and pregabaline was initiated as second to fourth agent. Therefore, comparison is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swisher and co-workers reported a success rate of 52% for pregabalin. 2 However, they included patients with acute repetitive seizures as well as patients with post-hypoxic SE, and pregabaline was initiated as second to fourth agent. Therefore, comparison is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…If this approach fails, one of the rescue strategies is to introduce one of the oral anticonvulsants by nasogastric tube. Topiramate (TPM) 1,2 and pregabalin (PGB) 3,4 have been used in this situation with some degree of success.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study reported definite electroclincal response at 24 h in 5 of 11 patients after PGB 450 mg, and a possible response in 3 . Analysis of 21 patients with nonconvulsive repetitive seizures or SE described a 52% responder rate; this proved much higher in repetitive seizures (82%) than in SE (18%) (Swisher et al 2013).…”
Section: Pregabalin (Pgb)mentioning
confidence: 93%
“…As second-line therapy (if convulsions persist), valproic acid and levetiracetam are often recommended (1,2). Pregabalin is rarely used for status epilepticus but has been used as add-on treatment and for non-convulsive status epilepticus (35,36). Judging from the present obervations in rats, levetiracetam may be the best choice for drugresistant seizures because gain of consciousness was obtained in most rats with levetiracetam.…”
Section: Effects Of Anticonvulsant Treatment On Cholinergic Activationmentioning
confidence: 99%